Tamu tak Diundang: Hubungan antara Pengungsi Maluku dan Penduduk Lokal di Sulawesi Utara - Christopher R. Duncan (Antropologi Indonesia, 2004)
This paper looks at the deteriorating relations between the population of Sulawesi Utara and the approximately 35,000 internally displaced people (IDPs) who fled there from the neighboring province of Maluku Utara. These IDPs first began arriving in large numbers in November of 1999 when communal violence broke out on the islands of Ternate and Tidore in Maluku Utara. They continued arriving until the violence came to a halt in June of 2000.Initially, relations between the two groups were positive. However, the extended presence of 35,000 IDPs created several problems, including a decrease in wages and an increase in housing costs. Negative perceptions of IDPs and jealously over IDP aid have created further misunderstandings. Additionally, IDP experiences with locals have led them to distrust the local population. On a few occasions these tensions have broken out into violence, and some fear this is a foreshadowing of the future should large numbers of IDPs decide to stay in Sulawesi Utara. This paper examines the relationships between these groups, as well as some of the efforts made by international NGOs to address these issues.